Echocardiographic assessment of mediastinal tumor - a case report - Beata Krasuska; Wioletta Anna Bal; Weronika Sandra Topyła; Tomasz Krzysztof Bąk; Michał Trojnar (Kazimierz Wielki University, 2018)
The mediastinum is the central area of the thoracic cavity which is divided into anterior, middle and posterior section. Medisatinal masses are usually asymptomatic. They can be detected accidentally in planned imaging studies. Echocardiography is safe, cheap, quick and non-invasive investigation, which can be useful in the diagnosis of this type of changes.